2007
DOI: 10.1080/09515070701633283
|View full text |Cite
|
Sign up to set email alerts
|

Psychological type and counselling psychology trainees’ choice of counselling orientation

Abstract: Clarifying the factors which influence choice of counselling orientation is important. This study investigated whether psychological type is associated with choice of orientation in counselling psychology trainees. Sets of questionnaires were sent to 210 counselling psychology trainees in four universities, which resulted in a sample of 84 participants. The measures were the Keirsey Temperament Sorter II and a short demographic questionnaire which also asked open-ended questions about chosen orientation. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The current findings, in which 66% of person-centered counselors had a preference for feeling, lend some support to Erikson's assertion. A study by Varlami and Bayne (2007), involving counseling psychology students, commented that those who preferred SJ were more likely to choose the cognitive behavioral model; however, over a third (36.5%) of the counselors in the current study had a preference for SJ and their counseling approach was person-centered. It could be argued that the previous study involved counseling students who had not yet fully decided on their particular choice of counseling, and therefore were not fully aware of what the different approaches entailed.…”
Section: Discussionmentioning
confidence: 59%
“…The current findings, in which 66% of person-centered counselors had a preference for feeling, lend some support to Erikson's assertion. A study by Varlami and Bayne (2007), involving counseling psychology students, commented that those who preferred SJ were more likely to choose the cognitive behavioral model; however, over a third (36.5%) of the counselors in the current study had a preference for SJ and their counseling approach was person-centered. It could be argued that the previous study involved counseling students who had not yet fully decided on their particular choice of counseling, and therefore were not fully aware of what the different approaches entailed.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, newer studies confirmed the relationship between a theoretical orientation of a counselor or therapist, on the one hand, and the personality characteristics or philosophical worldview of a counselor or therapist (Poznanski & McLennan, 2003;Tremblay, Herron, & Schultz, 1986) or a trainee (Boswell, Castonguay, & Pincus, 2009;Buckman & Barker, 2010;Taubner, Kächele, Visbeck, Rapp, & Sandell, 2010;Varlami & Bayne, 2007) on the other.…”
Section: Choice and Development Of Theoretical Orientationmentioning
confidence: 81%
“…Skovholt & Rønnestad [39] found that beginning counseling students in the beginning stages of counselor development are not confident or comfortable in making clinical decisions. Theme 13 was also related to Sundland, and Barker [43] who found that theory selection is closely related to the experience of the therapist.…”
Section: Resultsmentioning
confidence: 99%